Return on Assets pada Perusahaan Makanan dan Minuman yang terdaftar di BEI: Studi Pengaruh Current Ratio dan Debt to Equity Ratio - Aginda Pratiwi; Fatmi Hadiani; Leni Nur Pratiwi (Indonesian Journal of Economics and Management, 2022)
The aim of this research are to analyze the effect of CR and DER to at food and Beverage listed on BEI (Indonesian Stock Exchange) Period 2014 – 2018.The method used is purposive sampling method is the technique of determinng the sample based on certain critria and considerations. With a total of 8 perusahaan for 5 years from 2014 - 2018. Completing this final project is quantitative. The analytical tool used in this study is with using the of Eviews 10 sofware. The research showed that CR (Current Ratio) are not having significant effect partially to ROA (Return On Assets), therefore, DER (Debt to Equity Ratio) are not having significant effect partially to ROA (Return On Assets), therefore, CR (Current Ratio) and DER (Debt to Equity Rato) are simultaneously react significanly to ROA (Return On Assets).